Pengaruh Kebisingan, Glukosa Darah, dan Indeks Massa Tubuh terhadap Kadar Laktat pada Pekerja Industri Tekstil - Sumardiyono Sumardiyono; Bachtiar Chahyadhi; Farhana Syahrotun Nisa Suratna; Rachmawati Prihantina Fauzi; Reni Wijayanti; Maria Paskanita Widjanarti; Yeremia Rante ‘Ada (Jurnal Penelitian Pendidikan IPA, 2023)
Occupational fatigue remains a prevalent concern in occupational health. This study investigated the association between noise intensity, blood glucose levels, body mass index (BMI), and lactate levels as an indicator of occupational fatigue among textile industry workers in Surakarta, Indonesia. An analytical observational study with a cross-sectional design was conducted, with 82 participants recruited from a local textile industry. Multivariate analysis using multiple binary logistic regression revealed that noise intensity, blood glucose levels, and BMI were significant risk factors for occupational fatigue, as indicated by elevated lactate levels. These findings highlight the importance of noise reduction measures, a healthy lifestyle, and regular monitoring of blood glucose levels and BMI to mitigate occupational fatigue among textile industry workers